Investigating the Low Temperature Formation of CuII‐(N, O) Species on Cu‐CHA Zeolites for the Selective Catalytic Reduction of NOx. Issue 46 (26th July 2018) - Negri, Chiara; Hammershøi, Peter S.; Janssens, Ton V. W.; Beato, Pablo; Berlier, Gloria; Bordiga, Silvia
Abstract: In this work, we show the potentiality of operando FTIR spectroscopy to follow the formation of Cu II ‐(N, O) species on Cu exchanged chabazite zeolites (Cu‐CHA), active for the selective catalytic reduction of NOx with NH3 (NH3 ‐SCR). In particular, we investigated the reaction of NO and O2 at low temperature (200 and 50 °C) on a series of Cu‐CHA zeolites with different composition (Si/Al and Cu/Al ratios), to investigate the nature of the formed copper nitrates, which have been proposed to be key intermediates in the oxidation part of the SCR cycle. Our results show that chelating bidentate nitrates are the main structures formed at 200 °C. At lower temperature a mixture of chelating and monodentate nitrates are formed, together with the nitrosonium ion NO +, whose amount was found to be proportional to the zeolite Brønsted site concentration. Nitrates were found to mainly form with Cu II ions stabilized by one negative framework charge (Z), Z‐[Cu(OH] I or Z‐[Cu(O2 ] I, without involvement of Z2 ‐Cu II ones. This evidence, together with the absence of bridging nitrates in samples with high probability for Cu–Cu pairs, indicate that the nitrate ligands are not able to mobilize copper ions, at variance with what recently reported for NH3 . Finally, water was found to replace preformed chelating copper nitrates and deplete NO + (though with different kinetics) at both temperatures, while favouring the presence of monodentate ones. Abstract : Back to the Cu SCR : Operando infrared spectroscopy shows that chelating bidentate structures are the main copper nitrates formed on Cu‐CHA when exposed to NO/O2 mixture at 200°C, while monodentate ones can be formed at 50°C and in presence of water. Nitrates formation only involves Cu II ions stabilized by one framework negative charge and does not favor ion mobility.